Sonia a biography - Kidwai, Rasheed (Penguin, 2003)
On the life and times of Sonia Gandhi, b. 1946; leader of the Congress Party and widow of Rajiv Gandhi, b. 1944, former prime minister of India.
Political biography of Sonia Gandhi, b. 1946, President of Indian National Congress
Keywords: Gandhi, Sonia <1946->; Gandhi, Sonia -- 1946-; Indian National Congress -- Biography; Politik; Politicians -- India -- Biography; Prime ministers' spouses -- India -- Biography; Indien; India -- Politics and government -- 1947-; Biografie